Analysis of Rock Mass Quality and Support Requirements Using Q-System – Case Study: Kalan Uranium Exploration Tunnel, West Kalimantan, Indonesia - Wira Cakrabuana; Indra Andra Dinata; Yuni Faizah; Dhatu Kamajati; Putri Rahmawati (EKSPLORIUM, 2025)
The Kalan uranium exploration tunnel was one of the nuclear minerals research facilities in Indonesia. This 618 m long tunnel, located in West Kalimantan, Indonesia, was built on Eko Remaja Hill and operated from 1980-2021. In this tunnel, uranium mineralization occurs as irregular veins (stockworks) in metasiltstone and metapelite. The high density of these veins causes the formation of several weak zones in the tunnel. These weak zones cause rock and soil failures at several locations in the tunnel. The study aims to evaluate the quality of the rock mass surrounding the tunnel and determine the support requirements necessary to prevent further structural failures. Scanline surveys were carried out in several zones that have not experienced failures to obtain Q-system parameters. Based on the results of the analysis, the rock mass that makes up the Kalan tunnel has a Q value of 0.61–48.22, so that it belongs to the class of very poor-very good rocks. By plotting the Q value with its equivalent dimension (ED) on the rock support chart, it is estimated that the support required by the tunnel is average bolt spacing without fiber-reinforced sprayed concrete. The ultimate pressures of the roof and wall support can bear are 0.04–0.24 MPa and 0.03–0.17 MPa, respectively.